LABOUR MIGRATION OF HEADS OF HOUSEHOLDS AND FAMILY STABILITY IN EBONYI STATE - Njemanze, Vivian Chizoma (African Journal of Social and Behavioural Sciences, 2024)
Labour migration of heads of households has multifaceted impacts on families, influencing emotional well-being and traditional gender roles. While migrant remittances can enhance family income and stability, the accompanying challenges are noteworthy. This paper examines the effects of labour migration on family stability in Ebonyi State, Nigeria. A sample of 125 family members, selected through purposive sampling, participated in the study by completing a self-administered questionnaire. Descriptive statistics and Chi-Square analysis were employed for data analysis. The study found that families experienced significant disruption, and frequent communication breakdown due to the heads of household’s absence, the heads of household’s migration have a positive impact on families’ financial well-being. Family members also experienced heightened emotional distress, lack of social support and increased workload due to the head of household’s migration as well as children in the family face challenges in their development. Interestingly, despite prevailing cultural norms, affected families did not substantially experience social stigma. This study implies that families are negatively affected by the head of household’s migration and that cultural norms and values do not shape the perception of the impact of migration. Concerted policy efforts are essential to mitigate the negative outcomes of labour migration. This includes establishing robust social support systems for families left behind and promoting family-friendly migration practices for migrants.